Role of coping strategies in the association between resilience and posttraumatic growth among cancer patients - Latif, Humera; Hussain, Farwa; Rehman, Abaid Ur; Samina Aisha (Medical Journal of South Punjab, 2024)
Objectives: The study aimed to explore the association between resilience, posttraumatic growth, and coping strategies among cancer patients. Moreover, the study also investigates the mediating role of coping strategies in the link between resilience and posttraumatic growth. Methodology: A cross-sectional study was conducted on a sample of 150 individuals who completed questionnaires, including the brief resilience scale, posttraumatic growth inventory, and brief cope. Result: The study revealed a positive relationship between resilience, Posttraumatic Growth (PTG), and coping strategies. Moreover, findings show that resilience is not predictive of higher Posttraumatic Growth (PTG). Conclusion: Posttraumatic growth is 23% mediated by emotion-focused coping strategies and patients have a tendency to use avoidance coping strategies which leads lower healthy growth.